Upgrading of recreational rowing centre for Majlis Pembandaran Taiping at Jalan Taman Tasik, Taman Tasik Taiping, 34000 Taiping, Perak Darul Ridzuan / Nur Fiqriah Fadzil - Fadzil, Nur Fiqriah (Faculty of Architecture, Planning and Surveying, 2011)
The final project for the student of Diploma in Interior Architecture is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. It also done to identify the level of understanding and applies all their knowledge into the final project. The project that i have been chosen is upgrading the Recreational Rowing Centre for Majlis Pembandaran Taiping. The site is located at Jalan Taman Tasik Taiping, Taman Tasik Taiping, 34000 Taiping, Perak. Taman Tasik Taiping is famous all around the world among the local and the foreign country tourist. It is also known as Malaysia’s First Botanical Wonderland. This upgrading project for the Recreational Rowing Centre is to attract local families and tourist especially to embrace the beauty and treasure the importance of nature. The target market for the users of this recreation centre are families and as a tourist attraction. Concept and image that had been chosen not only must be suitable with the clients but have to be friendly to the environment and users as both of it would reflect the country image itself. The methodology to do researches for this project is by visiting the other recreational centre, interviews and collecting information’s from the client itself, by having my own experience at this centre and getting more information from the electronic sources or media articles. The issues that have been detected is that the RRC does not resembles a good recreation centre, therefor people tend to unnoticed the centre. Moreover by upgrading the centre it could improve the Taiping’s city image itself and educate people about the importance of nature while getting close to it.